Genome triplication drove the diversification of Brassica plants. (21st May 2014) - Cheng, Feng; Wu, Jian; Wang, Xiaowu
Abstract: The genus Brassica belongs to the plant family Brassicaceae, which includes many important crop species that are used as oilseed, condiments, or vegetables throughout the world. Brassica plants comprise many diverse species, and each species contains rich morphotypes showing extreme traits. Brassica species experienced an extra whole genome triplication (WGT) event compared with the model plant Arabidopsis thaliana . Whole genome sequencing of the Brassica species Brassica rapa, Brassica oleracea and others demonstrated that WGT plays an important role in the speciation and morphotype diversification of Brassica plants. Comparative genomic analysis based on the genome sequences of B. rapa and A. thaliana clearly identified the WGT event and further demonstrated that the translocated Proto-Calepine Karyotype (tPCK, n =7) was the diploid ancestor of the three subgenomes in B. rapa . Following WGT, subsequent extensive genome fractionation, block reshuffling and chromosome reduction accompanied by paleocentromere descent from the three tPCK subgenomes during the rediploidization process produced stable diploid species. Genomic rearrangement of the diploid species and their hybridization then contributed to Brassica speciation. The subgenome dominance effect and biased gene retention, such as the over-retention of auxin-related genes after WGT, promoted functional gene evolution and thus propelled the expansion of rich morphotypes in the Brassica species. In conclusion, the WGT event initiated subsequent genomic and gene-level evolution, which further drove Brassica speciation and created rich morphotypes in each species. Crop species: Genome multiplication the source of Brassica diversity: Genome sequencing reveals the mechanisms underlying the diversity of Brassica, a plant genus with an astonishingly wide range of forms. Brassica (including turnips, cabbage and rapeseed) has triple the number of chromosomes of its closest relatives. Xiaowu Wang and colleagues at the Institute of Flowers and Vegetables in Beijing review the effects of this ancient whole-genome triplication (WGT) and describe how it underlies the evolution of both new species and morphological diversity in Brassica . The WGT initiated reorganisation of the entire genome, generating new species, while retention and differentiation of genes gained during the WGT, such as those coding for hormones, drove the evolution of new characteristics like swollen roots, leafy heads and oil-rich seeds. Understanding this genomic history may provide keys to future genetic improvement of cultivated Brassica .